Oral corticosteroid dosing regimen and long-term prognosis in generalised myasthenia gravis: a multicentre cross-sectional study in Japan. Issue 5 (24th November 2017) - Imai, Tomihiro; Utsugisawa, Kimiaki; Murai, Hiroyuki; Tsuda, Emiko; Nagane, Yuriko; Suzuki, Yasushi; Minami, Naoya; Uzawa, Akiyuki; Kawaguchi, Naoki; Masuda, Masayuki; Konno, Shingo; Suzuki, Hidekazu; et al.
Abstract : Objective: We examined the correlation between the dosing regimen of oral prednisolone (PSL) and the achievement of minimal manifestation status or better on PSL ≤5 mg/day lasting >6 months (the treatment target) in patients with generalised myasthenia gravis (MG). Methods: We classified 590 patients with generalised MG into high-dose (n=237), intermediate-dose (n=187) and low-dose (n=166) groups based on the oral PSL dosing regimen, and compared the clinical characteristics, previous treatments other than PSL and prognosis between three groups. The effect of oral PSL dosing regimen on the achievement of the treatment target was followed for 3 years of treatment. Results: To achieve the treatment target, ORs for low-dose versus high-dose regimen were 10.4 (P<0.0001) after 1 year of treatment, 2.75 (P=0.007) after 2 years and 1.86 (P=0.15) after 3 years; and those for low-dose versus intermediate-dose regimen were 13.4 (P<0.0001) after 1 year, 3.99 (P=0.0003) after 2 years and 4.92 (P=0.0004) after 3 years. Early combined use of fast-acting treatment (OR: 2.19 after 2 years, P=0.02; OR: 2.11 after 3 years, P=0.04) or calcineurin inhibitors (OR: 2.09 after 2 years, P=0.03; OR: 2.36 after 3 years, P=0.02) was associated positively with achievement of treatment target. Conclusion: A low-dose PSL regimen with early combination of other treatment options may ensure earlier achievement of the treatment target in generalised MG.